PRODUK DOMESTIK BRUTO DAN ELASTISITAS KESEMPATAN KERJA DI SUMATERA SELATAN - Rosmiyati Chodijah (Jurnal Ekonomi Pembangunan, 2007)
This research aim to analysing absorbtion of labour at economics sector in South Sumatera. Economics sector which intended in this research divided superior of three main sector, that is sector A ( agriculture), sector M ( manufacturing) and sector S (Services). Calculation which done to know elasticity absorbtion of labour at each sector reckoning at economics sector in South Sumatra, by comparing between Gross Domestic Bruto with amount of labor forces on the each sectors. Earnings yield which done give earnings yield that if known amount of populations and output increased hence will influence alteration of labor capable to being permeated at  each economicses sectors in South Sumatera. Key Words: Gross Domestic Bruto, Elasticity Of labor, labor capable